The Effect of Cost of Goods Manufactured, Sales Promotion, and Selling Price on Net Profit at MSMEs in Ilir Barat I Palembang District - Dinda Shellamitha; RM. Rum Hendramin; Aris Munandar (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study was to determine whether the cost of production, sales promotion, and selling price affect net income. The independent variables used in this analysis are the cost of production, sales promotion and selling price. Then there is also the dependent variable, namely net income. The type of research used is survey research with a quantitative approach originating from primary data. This research uses some micro, small and medium enterprises in Ilir Barat I District, Palembang as the sample. Samples were carried out using the slovin formula technique with a tolerance of 10%. Data collection was carried out by observation and questionnaires distributed directly to micro, small and medium enterprises as many as 96 respondents. The results of the study show that the results of simultaneous testing can be seen that Fcount > Ftable, so it can be concluded that the cost of production (X1), sales promotion (X2), and selling price (X3) have an effect on net profit (Y).